2022
DOI: 10.1159/000525698
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Automatic Computer Vision-Based Assessment of Orofacial Kinematics for Telehealth Applications

Abstract: <b><i>Introduction:</i></b> Telehealth/remote assessment using readily available 2D mobile cameras and deep learning-based analyses is rapidly becoming a viable option for detecting orofacial and speech impairments associated with neurological and neurodegenerative disease during telehealth practice. However, the psychometric properties (e.g., internal consistency and reliability) of kinematics obtained from these systems have not been established, which is a crucial next step before th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…This approach enabled us to make definitive comparisons between 2D camera-based facial tracking and gold standards; however, it is a cumbersome approach (e.g., labor-intensive to extract facial movements). Our previous work using a markerless method [31] generally supports our present findings, e.g., that facial tracking using markerless methods is reliable and can detect differences between tasks. This approach should be used in the future.…”
Section: Limitationssupporting
confidence: 91%
See 3 more Smart Citations
“…This approach enabled us to make definitive comparisons between 2D camera-based facial tracking and gold standards; however, it is a cumbersome approach (e.g., labor-intensive to extract facial movements). Our previous work using a markerless method [31] generally supports our present findings, e.g., that facial tracking using markerless methods is reliable and can detect differences between tasks. This approach should be used in the future.…”
Section: Limitationssupporting
confidence: 91%
“…This likely reflected the well-known phenomenon of the speed-distance trade-off, in which speed increases reflect a compensation for distance and timing requirements (wider aperture but normal rate) [36]. The present results provide additional support for our previous work, in which we analyzed task-related differences in orofacial kinematics and found that markerless facial tracking methods could distinguish between oromotor tasks [31] as well as detect disease [51].…”
Section: Validation Of Webcam-based Speech Data Collectionsupporting
confidence: 86%
See 2 more Smart Citations
“…Webcam data collection also permits the frame‐by‐frame automated facial expression analysis using machine learning algorithms that enable prototype matching using large training datasets. The potential for these methods to inform neurodevelopment is strong and, increasingly, both webcam‐collected data (Simmatis et al, 2023) and artificial intelligence/machine learning algorithms (Nerusil et al, 2021) are being applied to create novel biometric measures for assessing child development and neurological conditions. A key advantage of webcam‐based data collection is that the paradigms can be administered without direct real‐time clinical supervision.…”
Section: Introductionmentioning
confidence: 99%